Functional Interplay Between Murine Leukemia Virus Glycogag, Serinc5, and Surface Glycoprotein Governs Virus Entry, with Opposite Effects on Gammaretroviral and Ebolavirus Glycoproteins - Yadvinder S. Ahi (American Society for Microbiology, 2016)
ABSTRACT Gammaretroviruses, such as murine leukemia viruses (MLVs), encode, in addition to the canonical Gag, Pol, and Env proteins that will form progeny virus particles, a protein called “glycogag” (glycosylated Gag). MLV glycogag contains the entire Gag sequence plus an 88-residue N-terminal extension. It has recently been reported that glycogag, like the Nef protein of HIV-1, counteracts the antiviral effects of the cellular protein Serinc5. We have found, in agreement with prior work, that glycogag strongly enhances the infectivity of MLVs with some Env proteins but not those with others. In contrast, however, glycogag was detrimental to MLVs carrying Ebolavirus glycoprotein. Glycogag could be replaced, with respect to viral infectivity, by the unrelated S2 protein of equine infectious anemia virus. We devised an assay for viral entry in which virus particles deliver the Cre recombinase into cells, leading to the expression of a reporter. Data from this assay showed that both the positive and the negative effects of glycogag and S2 upon MLV infectivity are exerted at the level of virus entry. Moreover, transfection of the virus-producing cells with a Serinc5 expression plasmid reduced the infectivity and entry capability of MLV carrying xenotropic MLV Env, particularly in the absence of glycogag. Conversely, Serinc5 expression abrogated the negative effects of glycogag upon the infectivity and entry capability of MLV carrying Ebolavirus glycoprotein. As Serinc5 may influence cellular phospholipid metabolism, it seems possible that all of these effects on virus entry derive from changes in the lipid composition of viral membranes. IMPORTANCE Many murine leukemia viruses (MLVs) encode a protein called “glycogag.” The function of glycogag is not fully understood, but it can assist HIV-1 replication in the absence of the HIV-1 protein Nef under some circumstances. In turn, Nef counteracts the cellular protein Serinc5. Glycogag enhances the infectivity of MLVs with some but not all MLV Env proteins (which mediate viral entry into the host cell upon binding to cell surface receptors). We now report that glycogag acts by enhancing viral entry and that, like Nef, glycogag antagonizes Serinc5. Surprisingly, the effects of glycogag and Serinc5 upon the entry and infectivity of MLV particles carrying an Ebolavirus glycoprotein are the opposite of those observed with the MLV Env proteins. The unrelated S2 protein of equine infectious anemia virus (EIAV) is functionally analogous to glycogag in our experiments. Thus, three retroviruses (HIV-1, MLV, and EIAV) have independently evolved accessory proteins that counteract Serinc5.